Rubber wood market in India- Emerging changes - Haridasan V (Placrosym VII, Coonoor, 1986. Journal of Plantation Crops, 16(Supplement):141-145)
This paper tries to evaluate the contribution of rubber wood to the wood based industry in Kerala and Kanyakumari district of Tamilnadu. The main consumer of rubber wood is the packing case manufacturing industry, accounting for about 13.6 million cft.The present study has attempted to evaluate the consumption of rubber wood in other sectors of wood based industry viz. plywood, splinters, veneers, accessories to textile mills and furniture. Theses industries consumed about 93000 cmt of rubber wood. The main conclusion of the study is that the rubber wood is supplying about 68 per cent of the requirements of small scale wood based industry in Kerala.
Keywords: Rubber wood